Revision of the lysianassoid genera Acidostoma and Shackletonia (Crustacea: Amphipoda: Acidostomatidae fam. nov.) - Stoddart, H. E.; Lowry, J. K. (Zootaxa, 2012)
The new lysianassoid amphipod family Acidostomatidae is described for the widespread genus Acidostoma Lilljeborg, 1865and the endemic Antarctic genus Shackletonia K.H. Barnard, 1931. All species of Acidostoma are described including three new species. Acidostoma obesum (Bate & Westwood, 1861) is discussed in detail.